Chemo‐ and Stereodivergent Preparation of Terminal Epoxides and Bromohydrins through One‐Pot Biocatalysed Reactions: Access to Enantiopure Five‐ and Six‐Membered N‐Heterocycles - Bisogno, Fabricio Román (2010)
Different enantiopure terminal epoxides or bromohydrins have chemoselectively been synthesised in one-pot starting from the corresponding a-bromo ketones through alcohol dehydrogenase (ADH)-catalysed processes adding an organic cosolvent and tuning appropriately the medium pH and the temperature. Thus, at neutral pH enantiopure bromohydrins were obtained while using basic conditions (pH 9.5–10) epoxides were isolated as the main product. Furthermore, by simple selection of the biocatalyst, chemo- and stereodivergent transformations were achieved to obtain, e.g., enantiopure prolinol or piperidin-3-ol.